1996
DOI: 10.1038/sc.1996.76
|View full text |Cite
|
Sign up to set email alerts
|

Posterior limbus vertebral lesions causing lumbosacral radiculopathy and the cauda equina syndrome

Abstract: JapanThis report reviews our experience with spinal decompression for posterior limbus vertebral lesions or osteocartilaginous vertebral corner defects in the lumbar spine in 29 children and young adults. There were 19 male and 10 female patients with a mean age of 16.5 years (range, 9 to 24 years). Twenty-four patients were involved with various athletic activities.Clinical presentation included low back pain with a variable degree of radiculopathy in 25 patients and a cauda equina syndrome in four. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
1
19
0
1
Order By: Relevance
“…The most common clinical presentations of lumbar PRAF are generally similar to those observed in patients with LDH alone, including intractable low back pain and unilateral or bilateral radiculopathy [1,10,12,13,16,28]. If spinal stenosis exists, intermittent claudication is complained [10,23,35]. The presenting symptoms and physical examination findings include paravertebral muscle spasm and tenderness, the presence of motor deficits or/and sensory disturbances, and the loss of a deep tendon reflex.…”
Section: Clinical Diagnosismentioning
confidence: 90%
See 4 more Smart Citations
“…The most common clinical presentations of lumbar PRAF are generally similar to those observed in patients with LDH alone, including intractable low back pain and unilateral or bilateral radiculopathy [1,10,12,13,16,28]. If spinal stenosis exists, intermittent claudication is complained [10,23,35]. The presenting symptoms and physical examination findings include paravertebral muscle spasm and tenderness, the presence of motor deficits or/and sensory disturbances, and the loss of a deep tendon reflex.…”
Section: Clinical Diagnosismentioning
confidence: 90%
“…Since the calcification and fusion process between ring apophysis and vertebral endplate may remain incomplete until the ages of 18-25, some studies thought the avulsion of this lesion was predominantly observed in the adolescents and young adults [4,23,26]. Takata et al [26] found that about half of the patients with PRAF were in their second decade of life, and most of the others were in their 20s.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations